A comprehensive review on PV configurations to maximize power under partial shading - Kho, Charles Tze Kang; Jubaer, Ahmed; Saad, Kashem; Then, Yi Lung (2017)
Partial shading is the condition where PV array experiences different level of irradiances on it which results significant reduction in output power. To handle that issue, PV modules are connected in various configurations as reported in the literature. Different connection schemes of the PV modules provide alternative paths to current flow that eventually improve power attainment under partial shading. A comprehensive study of literature shows that PV modules are connected under different schemes namely simple series (SS), parallel (P), series-parallel (SP), total-cross-tied (TCT), bridge-linked (BL) and honey-comb (HC). In this paper, a comprehensive review is performed to highlight the advantages and limitations of each scheme. To validate the findings from literature review, several experiments are carried out on various configurations in MATLAB Simulink. Three different cases namely unshaded, corner shaded and centre shaded conditions are used in the experiments to analyse the output characteristics. The superiority of various configurations in distinct operating conditions is demonstrated by comparing their maximum power output, relative power loss and fill factor. Based on the results, several recommendations are made on how to handle partial shading by using different PV configurations.